2019
DOI: 10.1039/c9cp01951k
|View full text |Cite
|
Sign up to set email alerts
|

An elevated concentration of MoS2 lowers the efficacy of liquid-phase exfoliation and triggers the production of MoOx nanoparticles

Abstract: The oxidation of MoS2 with a simultaneous decrease of MoS2 content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…After 50 min of laser treatment, the LSPR peaks vanish as the majority of the particles were transformed to MoO 3 nanobelts, as shown in the SEM (Figure 2d) and supported by the GIXRD pattern (Figure S1d) and Raman spectrum (Figure 3a). Additionally, the PL spectra (Figure S4a) show that the intensity of the PL peak at around 400 nm, which is attributable to MoO X , 14,32 increases with laser treatment time. The Tauc plot of the sample after 50 min of laser treatment is presented in Figure S4b.…”
Section: Resultsmentioning
confidence: 99%
“…After 50 min of laser treatment, the LSPR peaks vanish as the majority of the particles were transformed to MoO 3 nanobelts, as shown in the SEM (Figure 2d) and supported by the GIXRD pattern (Figure S1d) and Raman spectrum (Figure 3a). Additionally, the PL spectra (Figure S4a) show that the intensity of the PL peak at around 400 nm, which is attributable to MoO X , 14,32 increases with laser treatment time. The Tauc plot of the sample after 50 min of laser treatment is presented in Figure S4b.…”
Section: Resultsmentioning
confidence: 99%
“…SoMs are not limited to MoS 2 but are found in all Group IV–VII LTMDs, indicating a general hydrolytic decomposition pathway. Therefore, as-received powders, depending on storage conditions, contain a broad compositional and structural distribution of SoMs. Many research groups have reported blue discolorations during sonication assisted exfoliation of MoS 2 (in NMP, H 2 O/surfactant) and recommended a pretreatment step to remove undefined “surface impurities” before LTMDs can enter the liquid phase. Recent literature indicates that these impurities affect the colloidal stability of surfactant based exfoliation protocols due to their highly ionic character . To our knowledge, there have been no efforts to analyze these corrosion products.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As for the subphase, we used acidic water. The pH value was lowered to 4 to decrease the solubility of the MoS 2 in the subphase , by adding 5 mL of HCl to 500 mL of UPW. The surface of the subphase was carefully cleaned with a suction pump before applying the colloidal solution of the FL MoS 2 flakes.…”
Section: Methodsmentioning
confidence: 99%